Auto(trans)formação com professoras e professores na perspectiva da educação popular: o papel da escola e da gestão e os desafios do sistema educacional - Duttel, Cristiane Garcez Noronha (2021)
This dissertation presented to the Professional Master's Degree in Public Policy and Educational Management, was developed in the Pedagogical Management and Educational Contexts Research Line of the Education Center – UFSM. The study was carried out on the theme of permanent training research with teachers, through the epistemological-political proposal developed in the Dialogus Research Group: Education, Training and Humanization with Paulo Freire, called Dialogical Investigative-auto(trans)formative Circles . Meetings with teachers, management, APM and COE enabled the development of Circles, where themes suggested by the group of co-authors were discussed, with the following objectives: Investigating and building processes of reflection, studies and proposals that help to understand and assume a possible proposal for permanent self(trans)formation. We discover together and organize possible contributions to school management and self(trans)formation with teachers, from the perspective of emancipation and humanization of children and adolescents who are less favored or silenced by society. We carried out approaches and/or distances from the pedagogical proposal of the school with popular education and we socialized the constructs of this research after the completion of the six Dialogical Circles. The study has a qualitative approach, is based on research-self(trans)formation and presents a hermeneutic approach based on the interpretation of the dialogues developed in the meetings. As a theoretical subsidy, the study was based on the works of Paulo Freire (2019) and Marie Christine Josso (2010), as well as other authors such as: Arroyo (2001), Brandão (2013), Casassus (2007), Gadamer (1997 ), Lück (2013), Henz (2015), Maturana (2010) and Signor (2006), among others. By placing myself in “Novas Andarilhagens” I realized that the school, despite carrying out assistance work, excels in the awareness of its students and the search for better living conditions and egalitarian educational opportunities. This does not mean that the institution identifies itself as an institution of popular education, as it does not present curricular guidelines and regulations in this education bias in the official school documents, such as the PPP and the institution's charter. As a product of the research, a letter of intent was written with many hands, as a proposal for Permanent Self(trans)training processes with teachers and the (re)construction of the institution's PPP as a continuation of the school's training process.